2011
DOI: 10.1007/s10534-011-9494-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary methylmercury on the zebrafish brain: histological, mitochondrial, and gene transcription analyses

Abstract: The neurotoxic compound methylmercury (MeHg) is a commonly encountered pollutant in the environment, and constitutes a hazard for wildlife and human health through fish consumption. To study the neurotoxic impact of MeHg on piscivorous fish, we contaminated the model fish species Danio rerio for 25 and 50 days with food containing 13.5 μg/g dry weight (dw) of MeHg (0.6 μg MeHg/fish/day), an environmentally relevant dose leading to brain mercury concentrations of 30 ± 4 μg of Hg g(-1) (dw) after 25 days of expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 45 publications
3
30
1
Order By: Relevance
“…Others have shown that polymorphisms in GSTA1 genes confer protection against immune activation by exposure to xenobiotics in vulcanization processes (Jonsson et al 2008), presumable because these polymorphisms reduce the enzyme inhibition induced by xenobiotic compound binding to the enzyme (El-Demerdash 2001). While heavy metal exposure and binding may decrease glutathione transferase (but not GSTA) enzymatic activity, exposure to mercury has been shown to increase expression of glutathione transferase mRNAs (Cambier et al 2012; Korashy and El-Kadi 2006) in cell culture and zebrafish model systems. However, these studies examined expression of the gene transcript or the protein itself rather than the development of autoantibodies reactive with the protein as we have reported here.…”
Section: Discussionmentioning
confidence: 99%
“…Others have shown that polymorphisms in GSTA1 genes confer protection against immune activation by exposure to xenobiotics in vulcanization processes (Jonsson et al 2008), presumable because these polymorphisms reduce the enzyme inhibition induced by xenobiotic compound binding to the enzyme (El-Demerdash 2001). While heavy metal exposure and binding may decrease glutathione transferase (but not GSTA) enzymatic activity, exposure to mercury has been shown to increase expression of glutathione transferase mRNAs (Cambier et al 2012; Korashy and El-Kadi 2006) in cell culture and zebrafish model systems. However, these studies examined expression of the gene transcript or the protein itself rather than the development of autoantibodies reactive with the protein as we have reported here.…”
Section: Discussionmentioning
confidence: 99%
“…MeHg can cross the blood-brain barrier and accumulate to a significant degree in the brain and induce neurotoxicity (Kerper et al 1992; Berntssen et al 2003; Gonzalez et al 2005). Research in rainbow trout (Giblin et al 1973) and zebrafish (Cambier et al 2010, 2012) shows that MeHg can accumulate in lens, brain, skeletal muscle, blood and spleen. Recent research in spotted dogfish ( Scyliorhinus canicula ) shows that the bioaccumulation of mercury followed the order muscle > heart > liver > gills > pancreas (Coelho et al 2010).…”
Section: Discussion and Summarymentioning
confidence: 99%
“…Quantitative PCR (qPCR) can be used to evaluate alterations in gene expression [198]; however, the information is limited to the number of genes investigated.…”
Section: Evaluation Of Neurotoxicitymentioning
confidence: 99%
“…Methylmercury is associated with Minamata disease and nervous system impairment. Cambier et al [198] fed adult male fish food contaminated with methylmercury and found changes in gene expression in the GABA synthesis and metabolism pathways. Inorganic mercury is associated with acute toxicity and renal failure; however, Richetti et al [262] found that adult zebrafish exposed to mercury chloride and lead acetate had decreased activity of acetylcholinesterase, but no alterations in the gene expression of AChE.…”
Section: Specific Examples Of Chemical Toxicity Targeting Neurotramentioning
confidence: 99%